Repurchase aggrements - Thornham, Roger (London : Euromoney Publications [production company] ; London : Financial i Production [distributor], 1994)
The video focusses the US market for repurchase agreements - or'repos' that has grown in line with the increasing range of debt securities
Produced in association with Cedel and Swiss Bank Corporation
Copy available in DVD format
Executive producer, Colin G Sullivan ; writer, Warren Smith
Keywords: Repurchase agreements -- United States; Securities -- Prices